Comparative analysis of two strength training protocols on throwing speed in women's handball - Mariana Gómez-Ferolla; Andrés Santiago Parodi Feye; Carlos Magallanes-Mira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Shooting represents a fundamental skill in handball. Among other factors, its effectiveness requires a significant development of explosive strength. Isometric training may provide a powerful neuromuscular stimulus for its enhancement. Despite its importance and practicality, few studies have addressed the effect of this type of training on shooting speed in women's handball. Twenty female players were divided into two groups: isometric training (GI, n=10) and dynamic training (GD, n=10). Over nine weeks, twice a week, both groups completed an upper limb pushing resistance training: GI performed maximum isometric strength, and GD performed dynamic strength at 80% of one maximum repetition (1MR). In both cases, the effort was followed by medicine ball throws. The loads for both groups were equated in terms of sets and duration. Pre- and post-intervention, the 1MR of each player was estimated through a load progression test in bench press exercise. Additionally, the shooting speed with and without aiming at a target was measured from seven and nine meters using a radar. The findings showed a trend towards improvement in both groups (slightly higher in GI); however, only the not-targeted shooting speed from 9 meters in GI reached statistical significance (p < .05). The correlation between 1MR and shooting speed was low to moderate. In summary, both types of training yielded similar results. Given the practical advantages of isometric training, it could be suggested that this training could serve as an effective and practical alternative for enhancing strength and shooting speed in handball.